Damage control surgery for the treatment of perforated acute colonic diverticulitis: A systematic review. Issue 48 (25th November 2020) - Zizzo, Maurizio; Castro Ruiz, Carolina; Zanelli, Magda; Bassi, Maria Chiara; Sanguedolce, Francesca; Ascani, Stefano; Annessi, Valerio
Abstract: Background: Acute colonic diverticulitis (ACD) complications arise in approximately 8% to 35% patients and the most common ones are represented by phlegmon or abscess, followed by perforation, peritonitis, obstruction, and fistula. In accordance with current guidelines, patients affected by generalized peritonitis should undergo emergency surgery. However, decisions on whether and when to operate ACD patients remain a substantially debated topic while algorithm for the best treatment has not yet been determined. Damage control surgery (DCS) represents a well-established method in treating critically ill patients with traumatic abdomen injuries. At present, such surgical approach is also finding application in non-traumatic emergencies such as perforated ACD. Thanks to a thorough systematic review of the literature, we aimed at achieving deeper knowledge of both indications and short- and long-term outcomes related to DCS in perforated ACD. Methods: We performed a systematic literature review following the Preferred Reporting Items for Systematic Reviews and Meta-Analyzes (PRISMA) guidelines. Pubmed/MEDLINE, Embase, Scopus, Cochrane Library, and Web of Science databases were used to search all related literature. Results: The 8 included articles covered an approximately 13 years study period (2006–2018), with a total 359 patient population. At presentation, most patients showed III and IV American Society of Anesthesiologists (ASA) score (81.6%) while having Hinchey III perforated ACD (69.9%). Most patients received a limited resection plus vacuum-assisted closure at first-look while about half entire population underwent primary resection anastomosis (PRA) at a second-look. Overall morbidity rate, 30-day mortality rate and overall mortality rate at follow-up were between 23% and 74%, 0% and 20%, 7% and 33%, respectively. Patients had a 100% definitive abdominal wall closure rate and a definitive stoma rate at follow-up ranging between 0% and 33%. Conclusion: DCS application to ACD patients seems to offer good outcomes with a lower percentage of patients with definitive ostomy, if compared to Hartmann's procedure. However, correct definition of DCS eligible patients is paramount in avoiding overtreatment. In accordance to 2016 WSES (World Society of Emergency Surgery) Guidelines, DCS remains an effective surgical strategy in critically ill patients affected by sepsis/septic shock and hemodynamical unstability. Abstract : Supplemental Digital Content is available in the text